Pi-Expanded Coumarins with Switchable Propeller Geometries - Hintz, Heather A.; Sortedahl, Nicholas J.; Dahl, Bart J. (My University, 2017)
The focus of this project is analyzing planar conjugated molecules as molecular geometric switches. Our mission is to synthesize and study different classes of pi-expanded oligocoumarins with Crankshaft and Propeller architectures. The aryl-aryl torsional angle of the oligopheny subunits is controlled by lactone bridging groups to force planar conjugation. The lactone bridges could be reversibly cleaved and re-formed by changes in pH to form an open and closed conformation. Planar compounds with extended pi-conjugation suffer from poor solubility due to strong pi-stacking interactions. The synthesis with various solubilizing groups and switching studies of these compounds could lead to applications in areas such as organic electronics, molecular machines, light-harvesting materials, drug administration and sensors.
Color poster with text and images.
Keywords: Lactones; Molecular structure; Posters